Diseño de la estructura de una Impresora 3d didáctica de gran escala (2021)
3D printing is an application that has been used in the industry for the manufacture of parts. It allows the prototyping of custom designs and complex geometries. In the Santo Tomás University, in Tunja, the need to improve the quality of the projects in the research and classroom areas has been seen. A larger-scale 3D printer was designed, with respect to those that the university has; which conserves the quality, the resistance of the pieces and the metrological precision. Advantages and disadvantages were evaluated of the design alternatives. Its stability, stress resistance and volumetric capacity, were mainly analyzed. In addition, equipment for manufacturing will be taken into account, such as the 3D printer and chip startup machines that the university already has. The final design emerges and demonstrates the possibility of manufacturing a low-cost 3D printer with similar characteristics, compared to those found in the market; using affordable materials and manufacturing methods. In addition to the union of prototyped components with commercial parts., fulfilling optimal functionality.